EP580 Metformin may attenuate the effect of hyperprolactinemia induced by medroxyprogesterone acetate during fertility-sparing treatment for patients with atypical endometrial hyperplasia and endometrial cancer. (1st November 2019) - Mitsuhashi, A; Gu, W; Habu, U; Kobayashi, T; Shozu, M
Abstract : Introduction/Background: Prolactin (PRL) expression has been reported to stimulate cell proliferation and might be associated with worse survival outcomes in patients with endometrial cancer (EC). We evaluated the effect of PRL during medroxyprogesterone acetate (MPA) plus metformin treatment as fertility-sparing treatment in patients with atypical endometrial hyperplasia (AEH) and EC. Furthermore, we investigated the interaction of PRL and metformin on EC cells. Methodology: We retrospectively investigated 18 patients with AEH and 41 with EC who were treated with MPA (400 mg/day) plus metformin (750–2250 mg/day) as fertility-sparing treatments. We evaluated serum PRL levels before and during MPA administration. We analyzed the association between serum PRL and relapse-free survival (RFS). The EC-cell lines (ISHIKAWA, HEC-1B, and HEC 265) were treated with recombinant human PRL (500ng/ml) and/or metformin (1 mM). The interaction of PRL and metformin on EC cell proliferation was examined with a WST-8 assay and western blot analysis. Results: Before MPA treatment, the median serum PRL levels were 10.3 (4.5–47.0) ng/ml. During MPA treatment, the median serum PRL level increased to 34.6 (17.8–78.7) ng/ml. The percent of patients with hyperprolactinemia (>15 ng/ml) increased from 19% to 100% after starting MPA treatment. There was no significant difference in RFS between the patients with serum PRL levels ≥15 ng/ml and <15 ng/ml before MPA/metformin treatment and between those with serum PRL levels ≥30 ng/ml and <30 ng/ml during treatment. PRL promoted the proliferation and significantly increased phospho-ribosomal protein S6 and phospho-extracellular signal-regulated kinase 1/2 in EC cell lines. These effects were attenuated by the combination with metformin. Conclusion: High-dose MPA using fertility sparing treatment induced hyperprolactinemia that may cause a progressive effect on EC. The addition of metformin may prevent this effect and improve fertility-sparing treatment outcomes for patients with AEH and EC. Disclosure: Nothing to disclose.